Heart Rhythm Insights Into Structural Remodeling in Atrial Tissue: Timed Automata Approach - Makowiec, Danuta; Wdowczyk, Joanna; Struzik, Zbigniew R. (Frontiers in Physiology, 2019)
The heart rhythm of a person following heart transplantation (HTX) is assumed to display an intrinsic cardiac rhythm, because it is significantly less influenced by the autonomic nervous system --- the main source of heart rate variability in healthy people. Therefore, such a rhythm provides evidence for arrhythmogenic processes developing, usually silently, in the cardiac tissue. A model is proposed to simulate alterations in the cardiac tissue and to observe the effects of these changes on the resulting heart rhythm. The hybrid automata framework used makes it possible to represent reliably and simulate efficiently both the electrophysiology of a cardiac cell and the tissue organization. The curve fitting method used in design of the hybrid automaton cycle follows the physiologically well recognized phases of the atrial myocyte membrane excitation. Moreover, knowing of complex architecture of the right atrium, the ability of the almost free design of inter cellular connections makes the automata approach the only possible. Two particular aspects are investigated: impairment of the impulse transmission between cells and structural changes in intercellular connections. The first aspect models the observed fatigue of cells due to specific cardiac tissue diseases. The second aspect simulates the increase in collagen deposition with aging. Finally, heart rhythms arising from the model are validated with the sinus heart rhythms recorded in HTX patients. The modulation in the impairment of the impulse transmission between cells reveals qualitatively the abnormally high heart rate variability observed in patients long living after HTX.